Separator and lithium secondary battery comprising same

By using a porous substrate and a separator containing a coating of polyethylene oxide, nitrogen-containing water-soluble polymers and inorganic particles in lithium secondary batteries, the problems of fire, explosion and shortened life of lithium secondary batteries at high temperatures are solved. problem, achieving higher storage stability and long life.

CN119340613APending Publication Date: 2025-01-21SK INNOVATION CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410975970.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-20
Filing Date
2024-07-19
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Lithium secondary batteries are prone to fire or explosion when stored at high temperatures, and their lifespan is shortened, so it is difficult for the prior art to effectively solve these problems.

Method used

A separator composed of a porous substrate and a coating containing polyethylene oxide, nitrogen-containing water-soluble polymers and inorganic particles. This structure improves the high-temperature storage characteristics and battery life of lithium secondary batteries.

Benefits of technology

It significantly reduces the amount of gas generated by lithium secondary batteries at high temperatures and improves the high-temperature storage stability and long-term life characteristics of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004954517950000101
    Figure BDA0004954517950000101
  • Figure BDA0004954517950000111
    Figure BDA0004954517950000111
  • Figure BDA0004954517950000112
    Figure BDA0004954517950000112
Patent Text Reader

Abstract

The invention relates to a separator and a lithium secondary battery including the same. The present invention relates to a separator for a lithium secondary battery, and more specifically, to a separator for a lithium secondary battery having excellent high-temperature storage stability and capacity retention rate, low resistance increase rate, and significantly reduced gas generation amount, and a lithium secondary battery including the same. As one aspect, provided is a separator comprising a porous substrate and a coating layer formed on one or both surfaces of the porous substrate, the coating layer comprising inorganic particles and a water-soluble composite binder, and the water-soluble composite binder comprising polyoxyethylene and a nitrogen-containing water-soluble polymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a separator and a lithium secondary battery including the same. Background Art

[0002] Recently, there is a demand for lithium secondary batteries to have larger capacity so as to be applicable to electric vehicles, energy storage devices, etc. However, the larger the capacity of a lithium secondary battery, the higher the risk of fire and explosion. Therefore, various studies are being conducted to improve such problems.

[0003] Conventional lithium secondary batteries are manufactured by winding a battery cell consisting of a negative electrode, a positive electrode, and a separator between the negative electrode and the positive electrode into a cylinder or stacking and inserting it into a bag, and injecting a liquid electrolyte into the bag. The electrolyte plays a role in enabling the smooth movement of charges between the electrodes, and generally includes a non-aqueous organic solvent and a salt.

[0004] When a lithium secondary battery containing a non-aqueous organic solvent and a salt is stored at high temperature for a long time, the lithium secondary battery may catch fire or explode due to various factors.

[0005] As an example, in a lithium secondary battery using a carbonate organic solvent, a negative electrode passivation film (SEI film; solid electrolyte interphase film) is formed on the negative electrode surface as a decomposition product of a solid electrolyte, resulting in the decomposition of the carbonate organic solvent, thereby generating gas inside the secondary battery. Alternatively, the electrolyte is very sensitive to moisture and can generate gas. Depending on the type of non-aqueous organic solvent and negative electrode active material, such gas includes hydrogen (H2), carbon monoxide gas (CO2), methane gas (CH4), hydrogen fluoride, hydrogen sulfide, etc.

[0006] Due to the generation of this gas, the thickness expands during charging. When the lithium secondary battery is charged to the maximum capacity and placed at high temperature, a side reaction between the electrolyte and the negative electrode surface may occur, which will continue to generate gas, causing the internal pressure of the lithium secondary battery to increase and the volume to expand. Therefore, the performance of the lithium secondary battery will be reduced, such as the life of the lithium secondary battery at high temperature.

[0007] Therefore, in order to improve the problems of shortened life and degraded performance, research is being continued, such as changing the composition of the electrolyte or changing the type of negative electrode material. Summary of the invention

[0008] Technical issues

[0009] According to one aspect of the present disclosure, an object is to provide a separator capable of simultaneously improving high temperature storage characteristics and battery life of a lithium secondary battery.

[0010] Another object is to provide a separator capable of significantly reducing the amount of gas generated and a lithium secondary battery using the same.

[0011] The diaphragm disclosed herein and the lithium secondary battery including the same can be widely used in electric vehicles, battery charging stations, other green technology fields such as solar power generation and wind power generation using batteries. In addition, the diaphragm disclosed herein and the lithium secondary battery including the same can be used in eco-friendly electric vehicles and hybrid vehicles that prevent climate change by suppressing air pollution and greenhouse gas emissions.

[0012] Technical Solution

[0013] One aspect of the present disclosure provides a diaphragm comprising a porous substrate and a coating on one or both surfaces of the porous substrate, wherein the coating comprises a water-soluble composite binder comprising polyethylene oxide and a nitrogen-containing water-soluble polymer and inorganic particles.

[0014] In one aspect, the nitrogen-containing water-soluble polymer may include any one or two or more of the group consisting of polyvinyl pyrrolidone, polyvinyl pyrrolidone copolymers and polyacrylamide resins.

[0015] As one aspect, the polyacrylamide-based resin may be a copolymer including a unit derived from a (meth)acrylamide-based monomer and a unit derived from a comonomer.

[0016] As one aspect, the polyacrylamide resin may include (a) structural units derived from (meth)acrylamide monomers, (b) structural units derived from hydroxyl-containing (meth)acrylic acid monomers, and (c) structural units derived from multifunctional (meth)acrylamide monomers, but are not limited thereto.

[0017] As an aspect, the polyacrylamide resin may include (a) 65 to 96 mol% of structural units derived from (meth)acrylamide monomers, (b) 3 to 34 mol% of structural units derived from hydroxyl-containing (meth)acrylic monomers, and (c) 0.001 to 1 mol% of structural units derived from multifunctional (meth)acrylamide monomers, but is not limited thereto.

[0018] In one aspect, the polyacrylamide resin may have a weight average molecular weight of 100,000 to 2,000,000 g / mol, but is not limited thereto.

[0019] In one aspect, the inorganic particles may include at least one selected from boehmite and barium sulfate.

[0020] As an aspect, the inorganic particles may further include one or more inorganic particles selected from alumina, silica, aluminum hydroxide, magnesium hydroxide, calcium oxide, magnesium oxide, titanium oxide, aluminum nitride, SrTiO3, SnO2, CeO2, NiO, ZnO, ZrO2, Y2O3 and SiC, in addition to any one selected from boehmite and barium sulfate or a mixture thereof, but are not limited to this.

[0021] In one aspect, the inorganic particles may be a mixture of two or more inorganic particles having different average particle sizes.

[0022] As one aspect, the average particle size of the inorganic particles may be 200 to 1000 nm, without limitation thereto.

[0023] As one aspect, the weight ratio of the inorganic particles to the water-soluble composite binder in the coating layer may be 50 to 99.9:50 to 0.1, but is not limited thereto.

[0024] As one aspect, the content of the polyethylene oxide may be 1 to 50% by weight of the total content of the water-soluble composite adhesive, but is not limited thereto.

[0025] As one aspect, the content of the polyethylene oxide and the nitrogen-containing water-soluble polymer can be 10 to 90:90 to 10 by weight, but is not limited thereto.

[0026] As an aspect, the water-soluble composite adhesive may also include any one or more resins selected from the group consisting of polyvinyl acetate, acrylic resin, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-trichloroethylene copolymer, polyvinylidene fluoride-trifluorochloroethylene copolymer, polymethyl methacrylate, polyacrylonitrile, ethylene vinyl acetate copolymer, carboxymethyl cellulose, polyimide, etc., but is not limited thereto.

[0027] As one aspect, the thickness of the coating layer may be 0.1 to 50% of the total thickness of the separator, without limitation thereto.

[0028] As one aspect, the coating may be formed to have a thickness of 0.5 to 10 g / m 2 , but not limited to this.

[0029] In one aspect, the porous substrate may be any one selected from the group consisting of porous films, nonwoven fabrics, and woven fabrics, or a stack of two or more thereof, but is not limited thereto.

[0030] In one aspect, the thickness of the porous substrate may be 1 to 80 μm, but is not limited thereto.

[0031] Still another aspect of the present disclosure provides a lithium secondary battery including the separator according to the one aspect.

[0032] Technical Effects

[0033] The separator according to one aspect of the present disclosure can provide the effects of low heat shrinkage, excellent permeability, and excellent adhesiveness.

[0034] In addition, a lithium secondary battery using the separator according to one aspect of the present disclosure has a high capacity retention rate and a low resistance increase when stored at high temperatures, and thus can provide an effect of excellent high temperature storage stability.

[0035] In addition, a lithium secondary battery using the separator according to one aspect of the present disclosure has a high capacity retention rate and a low resistance increase rate in 400 cycle characteristics, and thus can provide an effect of excellent long-term battery capacity.

[0036] In addition, a lithium secondary battery using the separator according to one aspect of the present disclosure may provide an effect of being able to significantly reduce the amount of gas generation. DETAILED DESCRIPTION

[0037] The present disclosure is described in detail below, but this is merely an example, and the present disclosure is not limited to the specific embodiments described exemplarily.

[0038] In addition, unless otherwise defined, all technical terms and scientific terms have the same meaning as commonly understood by one of ordinary skill in the art. In the present disclosure, the terms used in the description are only for effectively describing specific examples and are not intended to limit the present disclosure.

[0039] In addition, unless otherwise indicated herein, singular forms used in the specification and the appended claims may also be intended to include plural forms.

[0040] Furthermore, when a part is described as “including” a part, unless otherwise stated, it means that other components may be included, rather than excluding other components.

[0041] In addition, unless otherwise defined, when a certain layer or component is mentioned as being on another “layer” or “component”, it not only includes the case where the certain layer or component is in contact with other layers or components, but also includes the case where other layers or other components are between the two layers or components.

[0042] In addition, the words "approximately", "substantially", etc. are used to mean a numerical value or a value close to the numerical value when the inherent manufacturing and material tolerances are proposed in the above meaning, and are used to prevent malicious intruders from improperly using the public content that describes precise or absolute numerical values ​​to help understand the present disclosure.

[0043] In this disclosure, average particle size refers to "D 50 "D50 " is a cumulative fraction based on volume, which refers to the particle size of 50% of the inorganic particles. The D can be derived from the particle size analysis results of sampling the inorganic particles to be measured according to the KS A ISO 13320-1 standard and analyzing them with the Multisizer 4e Coulter counter of Beckman Coulter. 50 .

[0044] In the present disclosure, the glass-transition temperature (Tg) refers to a temperature range in which glass transition occurs, and refers to a value measured using a dilatometer or a differential scanning calorimeter (DSC).

[0045] Unless otherwise specified in the present disclosure, the weight average molecular weight (Mw), number average molecular weight (Mn) and viscosity average molecular weight (Mv) can be measured by methods known in the art, such as polyethylene glycol-converted molecular weight analyzed by gel permeation chromatography (GPC).

[0046] In the present disclosure, "as a main component" means using as the main component compared to other components, for example, using 50 weight % or more, more specifically using 55 weight % or more, 60 weight % or more, 65 weight % or more, 70 weight % or more, 75 weight % or more, 80 weight % or more, 90 weight % or more, or 99 weight % or more.

[0047] According to one aspect of the present disclosure, a coating layer composed of a specific binder combination is formed, thereby providing a separator having excellent heat resistance, adhesion and air permeability. When using the separator, a lithium secondary battery with improved high-temperature storage characteristics and long-term life characteristics can be provided.

[0048] In addition, according to one aspect of the present disclosure, a coating is formed by combining a specific binder and a composition in which specific inorganic particles are combined, so that a lithium secondary battery with significantly reduced gas generation can be provided. Although not limited, when a lithium secondary battery using an electrolyte containing LiPF6 as an electrolyte is applied to the separator, the gas generation can be significantly reduced, but the type of electrolyte is not limited thereto.

[0049] One aspect of the present disclosure provides a diaphragm comprising a porous substrate and a coating formed on one or both sides of the porous substrate, wherein the coating comprises inorganic particles and a water-soluble composite adhesive, and the water-soluble composite adhesive comprises polyethylene oxide and a nitrogen-containing water-soluble polymer.

[0050] A first aspect of the separator according to the present disclosure is a separator comprising a porous substrate and a coating formed on one or both surfaces of the porous substrate, wherein the coating comprises a water-soluble composite binder comprising polyethylene oxide and a nitrogen-containing water-soluble polymer; and boehmite particles.

[0051] The second aspect is a diaphragm including a porous substrate and a coating formed on one or both surfaces of the porous substrate, wherein the coating includes a water-soluble composite binder including polyethylene oxide and a nitrogen-containing water-soluble polymer; and barium sulfate particles.

[0052] The third aspect is a diaphragm including a porous substrate and a coating formed on one or both sides of the porous substrate, wherein the coating includes a water-soluble composite binder including polyethylene oxide and a nitrogen-containing water-soluble polymer; and boehmite particles and barium sulfate particles.

[0053] The fourth aspect is a diaphragm comprising a porous substrate and a coating formed on one or both surfaces of the porous substrate, wherein the coating comprises a water-soluble composite adhesive comprising polyethylene oxide and a nitrogen-containing water-soluble polymer; and any one of boehmite particles and barium sulfate particles or their mixed particles and inorganic particles other than these.

[0054] The fifth aspect is a diaphragm comprising a porous substrate and a coating formed on one or both surfaces of the porous substrate, wherein the coating comprises a water-soluble composite adhesive comprising polyethylene oxide and a nitrogen-containing water-soluble polymer; and any one or a mixed particle selected from boehmite particles and barium sulfate particles, wherein the boehmite particles and barium sulfate particles can be independently a mixture of two or more particles having different average particle sizes.

[0055] The first to fifth aspects are merely examples for explaining one aspect of the present invention and are not limited thereto. In addition, other layers may be further included between the porous substrate and the coating, and the type of the further included layer is not particularly limited. In addition, the coating may also be a coating in which two or more layers of different types of coatings are stacked, without being limited thereto.

[0056] Hereinafter, each configuration of the present disclosure will be described in more detail.

[0057] [Porous substrate]

[0058] As one aspect, the porous substrate is commonly used in the art, and may be woven fabric, non-woven fabric, porous membrane, etc., and may be any one selected therefrom or a stack of two or more thereof, without being limited thereto.

[0059] The material of the porous substrate is not limited, but for example, polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyacetal, polyamide, polyimide, polycarbonate, polyetheretherketone, polyaryletherketone, polyetherimide, polyamideimide, polybenzimidazole, polyethersulfone, polyphenylene ether, cycloolefin copolymer, polyphenylene sulfide, polyethylene naphthalate, glass fiber, Teflon and polytetrafluoroethylene can be used, and it can be composed of any one or more resins selected from the group consisting of the above.

[0060] As an example, the porous substrate may use an adjustable polyolefin porous substrate to refine the pores, but is not limited thereto. The polyolefin porous substrate is generally manufactured in a film form, and is not limited as long as it is conventionally used as a separator for lithium secondary batteries, such as polyethylene, polypropylene, and copolymers thereof, but is not necessarily limited thereto.

[0061] The thickness of the porous substrate is not particularly limited, but from the perspective of increasing the capacity of the lithium secondary battery at the same volume, the thickness can be less than 100 μm, less than 90 μm, less than 80 μm, more than 1 μm, more than 5 μm, or any value between the above values, for example, it can be 1 to 80 μm, 1 to 70 μm, 5 to 50 μm, or 5 to 30 μm.

[0062] [coating]

[0063] The separator of the present disclosure includes a coating layer on one or both sides of the porous substrate.

[0064] In one aspect, the coating may be a coating that covers more than 50%, more than 60%, more than 70%, more than 80%, more than 90%, or 100% of the area of ​​the porous substrate.

[0065] The thickness of the coating is not particularly limited, but can be formed in the range of 0.1 to 50%, 0.5 to 45%, or 1 to 40% of the total thickness of the separator. For example, when the coating is formed on one side or both sides, each coating thickness can be formed to a thickness of 0.01 to 10 μm, 0.1 to 10 μm, 0.3 to 8 μm, 0.3 to 5 μm, or 1 to 4 μm, without limitation thereto.

[0066] The weight per unit area of ​​the coating may be 0.5 to 100 g / m 2 , 0.5 to 50 g / m 2 , 0.5 to 10 g / m2 , 0.5 to 8 g / m 2 or 0.5 to 5 g / m 2 , but is not necessarily limited to this.

[0067] In one aspect, the coating is formed of inorganic particles and a water-soluble composite binder, and may be a coating in which the inorganic particles are interconnected to form pores between the inorganic particles.

[0068] The coating is not limited, but the content of the inorganic particles and the water-soluble composite binder may be 50 to 99.9:50 to 0.1 weight ratio, 80 to 99.9:20 to 0.1 weight ratio, 90 to 99:10 to 1 weight ratio, or 95 to 99:5 to 1 weight ratio. In the case of the above range, it is preferable because it can provide a separator that can smoothly move lithium ions and exhibit heat resistance and less heat shrinkage, but is not limited thereto.

[0069] As one aspect, the coating can be formed by applying a slurry composition including inorganic particles and a water-soluble composite binder. For example, it can include inorganic particles, a water-soluble composite binder and a solvent, and the solid content can be 5 to 50 weight %, 5 to 45 weight % or 5 to 40 weight %, but is not limited thereto.

[0070] As one aspect, the water-soluble composite adhesive can make the inorganic particles adhere to each other and to the porous substrate. In addition, it can also significantly reduce the amount of gas generated while satisfying the high-temperature storage characteristics and long-term life characteristics of the lithium secondary battery desired in the present disclosure.

[0071] As one aspect of the present disclosure, the water-soluble composite adhesive comprises both polyethylene oxide and nitrogen-containing water-soluble polymer, thereby achieving the above effect. If only one of them is included, it may be difficult to simultaneously meet the high-temperature storage characteristics and long-term life characteristics.

[0072] In addition, it can also be included in the heat-resistant adhesive or water-dispersible adhesive commonly used in the art as needed. Specifically, for example, the water-soluble composite adhesive can contain polyethylene oxide and nitrogen-containing water-soluble polymer as main components. The meaning of including as the main component can be, for example, relative to the total content of the water-soluble composite adhesive, the sum of the content of polyethylene oxide and nitrogen-containing water-soluble polymer is 50 weight %, 60 weight %, 70 weight %, 80 weight %, 90 weight %, 100 weight % or any range between the values. For example, the water-soluble composite adhesive can contain polyethylene oxide and nitrogen-containing water-soluble polymer 80 to 100 weight %, 85 to 100 weight %, 90 to 100 weight %, 95 to 100 weight % or 98 to 100 weight %.

[0073] The heat-resistant adhesive or water-dispersible adhesive that can be further added can be used without restriction as long as it is usually used in the separator for bonding inorganic particles. For example, it can include any one or more resins selected from the group consisting of polyvinyl acetate, acrylic resin, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-trichloroethylene copolymer, polyvinylidene fluoride-chlorotrifluoroethylene copolymer, polymethyl methacrylate, polyacrylonitrile, ethylene vinyl acetate copolymer, carboxymethyl cellulose, polyimide, etc.

[0074] In one aspect, the polyethylene oxide is a polymer including an ethylene oxide (ethylene oxide) ethylene oxide structure as a repeating unit, and the polyethylene oxide may also be modified to introduce functional groups at the ends. For example, any one or more functional groups of the group consisting of -H, -OH, -OR (where R is a C1-C20 alkyl group), -COOH (acetate group), -NR2 (amine group, where R is hydrogen or a C1-C20 alkyl group) etc. may be introduced into both end groups or one end group, but the present invention is not limited thereto.

[0075] The polyethylene oxide is not limited thereto, but for example, may have a viscosity average molecular weight (Mv) of 100,000 to 1,000,000 g / mol, 200,000 to 900,000 g / mol, or 200,000 to 700,000 g / mol. Within the above range, the desired effect can be achieved, but the invention is not limited thereto. The viscosity average molecular weight can be measured by gel permeation chromatography (GPC) using polyethylene glycol as a reference substance.

[0076] The content of the polyethylene oxide is less than 50 weight % of the total content of the water-soluble composite adhesive, for example, 1 to 50 weight %, 1 to 45 weight %, 1 to 40 weight % or 1 to 35 weight %, which can be beneficial to achieving the desired effect, but is not limited thereto.

[0077] In one aspect, the polyethylene oxide and the nitrogen-containing water-soluble polymer may be used in a weight ratio of 10 to 90:90 to 10, a weight ratio of 10 to 50:90 to 50, or a weight ratio of 10 to 40:90 to 60, but is not limited thereto.

[0078] In one aspect, the nitrogen-containing water-soluble polymer may include any one or two or more selected from the group consisting of polyvinyl pyrrolidone, polyvinyl pyrrolidone-based copolymers, and polyacrylamide-based resins.

[0079] In one aspect, the nitrogen-containing water-soluble polymer may include a polyacrylamide resin, or may be a mixture of any one or more selected from the polyacrylamide resin, polyvinyl pyrrolidone, and polyvinyl pyrrolidone copolymers. In one aspect, when any one or more selected from polyacrylamide resin, polyvinyl pyrrolidone, and polyvinyl pyrrolidone copolymers are mixed as the nitrogen-containing water-soluble polymer, the content of the polyacrylamide resin as the main component may be. That is, the polyacrylamide resin may be used in an amount of 50% by weight or more, for example, 50 to 99.9% by weight of the nitrogen-containing water-soluble polymer.

[0080] The polyvinyl pyrrolidone is not limited, but, for example, can have a weight average molecular weight (Mw) of 10,000 to 1,000,000 g / mol, 20,000 to 900,000 g / mol, 30,000 to 700,000 g / mol, 40,000 to 500,000 g / mol. Within the above range, it is beneficial to achieve the desired effect, but is not limited thereto.

[0081] The polyvinyl pyrrolidone copolymer includes units derived from N-vinyl-2-pyrrolidone and units derived from comonomers, and the comonomers can be selected from the group consisting of aromatic vinyl monomers; cyanovinyl monomers; aromatic (meth)acrylates having an aryl group, an alkylaryl group or an arylalkyl group with a carbon number of 6 to 20; hydroxyl-containing (meth)acrylates; epoxy-containing (meth)acrylates; unsaturated carboxylic acids; and the like, or a mixture of two or more thereof, but is not limited thereto.

[0082] For example, the comonomer may be selected from aromatic vinyl monomers including styrene, p-methylstyrene, m-methylstyrene, p-ethylstyrene, m-ethylstyrene, p-chlorostyrene, m-chlorostyrene, p-chloromethylstyrene, m-chloromethylstyrene, vinyltoluene, vinylnaphthalene, etc.; cyano vinyl monomers including acrylonitrile, methacrylonitrile, etc.; phenyl (meth)acrylate, benzyl (meth)acrylate, 2-phenylethyl (meth)acrylate, 3-phenylpropyl (meth)acrylate, 4-phenylbutyl (meth)acrylate, 2-2-methylphenylethyl (meth)acrylate, 2-3-methylphenylethyl (meth)acrylate, 2-4-methylphenylethyl (meth)acrylate, ate) and the like having an aryl group, an alkylaryl group or an arylalkyl group having a carbon number of 6 to 20; (meth)acrylates containing a hydroxyl group such as 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 1,4-cyclohexanedimethanol mono(meth)acrylate; (meth)acrylates containing an epoxy group such as glycidyl acrylate and glycidyl methacrylate; unsaturated carboxylic acids such as acrylic acid and methacrylic acid; any one or a mixture of two or more of the group consisting of vinyl acetate, etc., but not limited thereto.

[0083] In addition, the polyvinyl pyrrolidone-based copolymer may be, for example, a polyvinyl pyrrolidone-polyvinyl acetate block copolymer, but is not limited thereto.

[0084] The polyvinyl pyrrolidone copolymer is not limited, but can have a weight average molecular weight (Mw) of 10,000 to 1,000,000 g / mol, 50,000 to 900,000 g / mol, or 50,000 to 500,000 g / mol, for example. The above range can help achieve the desired effect, but is not limited thereto.

[0085] As one aspect, the polyacrylamide-based resin may be a copolymer including a structural unit derived from a (meth)acrylamide-based monomer.

[0086] For example, it can be a copolymer of a (meth)acrylamide monomer and a comonomer. Examples of the comonomer include any one or more selected from (meth)acrylic acid, a hydroxyl-containing (meth)acrylic monomer, a multifunctional (meth)acrylamide monomer, etc., but are not limited thereto.

[0087] In one aspect, the polyacrylamide resin may include (a) structural units derived from (meth)acrylamide monomers, (b) structural units derived from hydroxyl-containing (meth)acrylic acid monomers, and (c) structural units derived from multifunctional (meth)acrylamide monomers. The (meth)acrylic acid refers to acrylic acid and / or methacrylic acid.

[0088] Compared to using a monomer derived from an acrylic amide monomer, the polyacrylamide resin uses a copolymer of the above three components, which can further reduce the high-temperature shrinkage rate and impart high-temperature storage stability, thereby providing a diaphragm with better heat resistance. In addition, the miscibility with the polyethylene oxide is better, the adhesion with the porous substrate is excellent, and the air permeability is reduced due to the use of the polyethylene oxide, the movement of lithium ions can be smoother, and a diaphragm with better gas reduction effect can be provided. In addition, the high-temperature storage stability and high-temperature capacity retention rate of the lithium secondary battery can be greatly improved.

[0089] As an aspect, the polyacrylamide resin may include (a) 65 to 96 mol % of structural units derived from (meth)acrylamide monomers, (b) 3 to 34 mol % of structural units derived from hydroxyl-containing (meth)acrylic monomers, and (c) 0.001 to 1 mol % of structural units derived from multifunctional (meth)acrylamide monomers.

[0090] The (a) (meth)acrylamide-based monomer polymerization unit of the polyacrylamide-based resin may be represented by the following Chemical Formula 1.

[0091] [Chemical formula 1]

[0092]

[0093] In the Chemical Formula 1, R1 is hydrogen or a C1 to C6 alkyl group.

[0094] The (b) hydroxyl-containing (meth)acrylic acid-based monomer polymerization unit of the polyacrylamide-based resin may be represented by Chemical Formula 2.

[0095] [Chemical formula 2]

[0096]

[0097] In the chemical formula 2, R2 is hydrogen or a C1 to C6 alkyl group. In addition, L1 is a C1 to C6 linear or branched alkylene group.

[0098] The (c) multifunctional (meth)acrylamide-based monomer polymerization unit may be generated by polymerization of a multifunctional monomer represented by the following Chemical Formula 3.

[0099] [Chemical formula 3]

[0100]

[0101] In the chemical formula 3, R1 and R2 are independently hydrogen or a C1 to C6 alkyl group, R is a C1 to C10 straight or branched hydrocarbon group, and a can be 2 to 6.

[0102] As an example, (a) (meth) acrylamide monomers may be 65 to 96 mol%, 66 to 95 mol%, 67 to 94 mol%, 68 to 93 mol%, 70.5 to 91.5 mol%. (b) hydroxyl-containing (meth) acrylic monomers may be 3 to 34 mol%, 4 to 33 mol%, 5 to 32 mol%, 6 to 31 mol%, 8 to 29 mol%. (c) multifunctional (meth) acrylamide monomers may be 0.001 to 1 mol%, and may be prepared with an adhesive having a content of 0.005 to 0.9 mol%, 0.01 to 0.5 mol%.

[0103] As an example, the polyacrylamide resin may be a cross-linked copolymer of acrylamide, hydroxyethyl acrylate and N-methylenebisacrylamide, but is not limited thereto.

[0104] The weight average molecular weight of the polyacrylamide resin can be more than 100,000 g / mol, more than 150,000 g / mol, more than 200,000 g / mol, more than 250,000 g / mol, less than 2,000,000 g / mol, less than 1,500,000 g / mol, less than 1,000,000 g / mol, or any value between the above values. For example, it can be 100,000 to 2,000,000 g / mol. Within the scope of satisfying the range, the adhesion between the porous substrate is more excellent, the heat shrinkage rate can be further reduced, and the high temperature storage stability and capacity retention rate of the lithium secondary battery can be further improved. Therefore, it is preferred, but not limited to this. The weight average molecular weight is the polyethylene glycol conversion average molecular weight measured by gel permeation chromatography (GPC).

[0105] For the polyacrylamide resin, the viscosity of the aqueous solution with a solid content of 10 wt% may be 3000 cps or less, 2500 cps or less, 2000 cps or less, or 1500 cps or less, but is not limited thereto. When the polyacrylamide resin is mixed with polyethylene oxide and inorganic particles to prepare a slurry within the above range, the viscosity of the slurry can be further reduced, and the coating property can be further improved, so it is preferred.

[0106] As one aspect, the solvent used in the slurry composition prepared to form the coating layer can be, for example, an aqueous solution prepared with water, to which solvents such as acetone, tetrahydrofuran, dimethylformamide and N-methyl-2-pyrrolidone can be further added as needed.

[0107] In one aspect, the inorganic particles are electrochemically stable, and any inorganic particles generally used to improve the heat resistance and heat shrinkage of a separator can be used without limitation.

[0108] As one aspect, the inorganic particles can be any one or their mixture selected from boehmite and barium sulfate, and by containing these, the air permeability is excellent when mixed with the water-soluble composite adhesive described above, and the gas reduction effect can be achieved better. In addition, the high temperature storage stability and capacity retention rate of lithium secondary battery can be achieved. In addition, the boehmite, barium sulfate or their mixture can be included as the main component as required, and other inorganic particles are further included in addition. That is, boehmite, barium sulfate or their mixture can be used with more than 50 weight %, more than 60 weight %, more than 70 weight %, more than 80 weight %, more than 90 weight %, more than 95 weight %, more than 99 weight %, and the content below 100 weight % in the inorganic particles content, and can be used with any numerical value between the numerical values ​​recorded above.

[0109] The inorganic particles that can be further added can be used without restriction as long as they are commonly used in this field. For example, they can further include one or more inorganic particles selected from aluminum oxide, silicon dioxide, aluminum hydroxide, magnesium hydroxide, calcium oxide, magnesium oxide, titanium oxide, aluminum nitride, SrTiO3, SnO2, CeO2, NiO, ZnO, ZrO2, Y2O3, SiC and clay.

[0110] The size of the inorganic particles is not limited, but, for example, in order to provide smooth coating and excellent electrical properties, the average particle size can be 50 nm or more, 100 nm or more, 200 nm or more, 300 nm or more, 1500 nm or less, 1000 nm or less, 800 nm or less, or any range between the above values. For example, it can be in the range of 100 to 1500 nm, 200 nm to 1000 nm, or 300 to 800 nm. The morphology of the inorganic particles is not limited, and can be spherical, elliptical, needle-shaped, etc.

[0111] As one aspect, boehmite, barium sulfate or a mixture thereof can be used as inorganic particles used together with the water-soluble composite adhesive, and the boehmite and barium sulfate can be a mixture of two or more particles having different average particle sizes. That is, two particles having different average particle sizes can be mixed for use. For example, two boehms having different average particle sizes can be used, or two barium sulfates having different average particle sizes can be used, or boehmite and barium sulfate having different average particle sizes can be used.

[0112] For example, when two or more inorganic particles with different average particle sizes are used, a first inorganic particle with a relatively large average particle size and a second inorganic particle with a relatively small average particle size can be mixed and used, and the average particle size of the first inorganic particle can be 200 to 500 nm, and the average particle size of the second inorganic particle can be 500 to 1000 nm, and the difference between the average particle sizes of the first inorganic particle and the second inorganic particle can be 100 nm or more, for example, 100 to 500 nm. The first inorganic particle and the second inorganic particle can be independently boehmite or barium sulfate.

[0113] In one aspect, after the inorganic particles are mixed with the water-soluble composite binder and the solvent to prepare the slurry composition, the inorganic particles may be fully pulverized using a ball mill or the like to pulverize the agglomerates.

[0114] The method of coating the slurry composition on the porous substrate is not particularly limited, but can be applied to one or both sides of the porous substrate by various methods such as roller coating, spin coating, dip coating, rod coating, die coating, slit coating, inkjet printing, etc. without limitation.

[0115] The separator according to one aspect of the present disclosure may show a change amount (ΔG) of air permeability as shown in Formula 1 below.

[0116] [Formula 1]

[0117] △G=G1-G2≤50

[0118] In Formula 1, G1 is the Gurley permeability of the separator including the coating layer, and G2 is the Gurley permeability of the porous substrate itself, measured according to ASTM D726, and the unit is sec / 100cc.

[0119] In Formula 1, it may be 50 sec / 100cc or less, 1 to 45 sec / 100cc, or 5 to 40 sec / 100cc. In the above range, the change in air permeability is significantly small, so the separator can have excellent air permeability.

[0120] According to one aspect of the present disclosure, when the diaphragm is placed in a hot air drying oven at 130°C for 60 minutes, the measured high-temperature shrinkage rate can be any value between 5%, 4%, 3%, 0.1%, 1% or more, or the values ​​recorded above in both the mechanical direction and the width direction. For example, it can be 1 to 5%. When the range is met, the heat resistance is excellent, so a diaphragm with thermal stability can be provided. In addition, when the range is met, the lithium secondary battery can have a better gas reduction effect and excellent high-temperature storage stability.

[0121] In addition, the separator according to one aspect of the present disclosure can provide the effect that the adhesive force between the inorganic particles and the porous substrate is excellent and the detachment of the inorganic particles is significantly reduced.

[0122] [Lithium secondary battery]

[0123] The lithium secondary battery according to one aspect of the present disclosure may be a lithium secondary battery including the separator of one aspect described above between a positive electrode and a negative electrode. Here, the positive electrode and the negative electrode may be any one commonly used in lithium secondary batteries without limitation.

[0124] Although not limited, the lithium secondary battery may include an electrolyte, such as a liquid electrolyte, and the liquid electrolyte may include a dissociable lithium salt and a non-aqueous solvent commonly used in the field. The type of the lithium salt is not limited, but in the case of the separator disclosed herein, in the electrolyte containing LiPF6, the amount of gas generated can be significantly reduced. However, it is not limited thereto, and any commonly used electrolyte can be applicable.

[0125] The embodiments of the present disclosure are further described below through specific experimental examples. The embodiments and comparative examples included in the experimental examples are only examples of the present disclosure, and do not limit the scope of the attached claims. Various changes and modifications can be made to the embodiments within the scope of the present disclosure and the technical concept, which is obvious to ordinary technicians in the field, and it is natural that these deformations and modifications belong to the scope of the attached claims.

[0126] The physical properties were evaluated as follows.

[0127] [Weight average molecular weight]

[0128] The measurement was carried out using GPC (Tosoh EcoSEC HLC-8320GPC Reflective Index detector). The GPC columns (GPC Column) used were Tskgel guard PWx, two TSKgel GMPWxl and TSKgel G2500PWxl (7.8x300mm), the solvent was 0.1M NaNO3 aqueous solution, and the standard was polyethylene glycol. The analysis was carried out at 40°C and a flow rate of 1mL / min.

[0129] [Evaluation of thermal shrinkage]

[0130] Cut the membrane into a square with a side of 10 cm and mark the width direction (TD, Transverse Direction) and machine direction (MD, Machine Direction). Place the sample in the center, put five pieces of paper on the top and bottom of the sample and wrap the four sides of the paper with tape. Place the paper-wrapped sample in a hot air drying oven at 130°C for 60 minutes. Then take out the sample and measure the membrane with a camera, and calculate the shrinkage in the length direction (MD, Machine Direction) and the shrinkage in the width direction (TD, Transverse Direction) using the following formula.

[0131] High temperature shrinkage in the longitudinal direction (%) = (length in the longitudinal direction before heating - length in the longitudinal direction after heating) / length in the longitudinal direction before heating × 100

[0132] Width direction high temperature shrinkage (%) = (width direction length before heating - width direction length after heating) / width direction length before heating × 100

[0133] [Gerlai air permeability]

[0134] The Gurley permeability was measured using a Toyoseiki Densometer according to ASTM D726. The time required for 100cc of air to pass through 1 square inch of the membrane was recorded in seconds. The unit is sec / 100cc.

[0135] [Horse manure paper adhesion test]

[0136] Cut the diaphragm into 50mm×50mm size and place it on the rubber pad with the inorganic layer facing downward. Place black horse manure paper (20mm×50mm×T 0.25mm) between the diaphragm and the rubber pad and apply a certain pressure (10g / cm 2 ). The black horse manure paper was forcibly pulled out to the side to check the degree of inorganic matter adhesion on the surface, and the adhesion was graded into A / B / C according to the following grade.

[0137] A: No adhesion

[0138] B: A small amount of inorganic matter adheres

[0139] C: The degree to which the adhesive and inorganic matter adhere together

[0140] [Thickness measurement method]

[0141] Thickness of the diaphragm: The diaphragm is stacked into 10 layers, and then the thickness is measured at any five points in the width direction using a thickness measuring instrument from Mitut oyo. Then the average thickness of the 10 layers of diaphragms is derived and divided by 10 to derive the overall average thickness of a single diaphragm.

[0142] Thickness of porous substrate: Regarding the average thickness of the porous substrate, the porous substrate is simply stacked into 10 layers, and then the thickness is measured at any five points in the width direction using a thickness measuring instrument from Mitutoyo Company. The average thickness of the 10 layers of porous substrates is then derived and divided by 10 to derive the average thickness of a single porous substrate.

[0143] Thickness of coating layer: The thickness of coating layer was derived by calculating the value obtained by subtracting the average thickness of individual porous substrates from the average thickness of the entire separator obtained by the above method.

[0144] [Example 1]

[0145] <Preparation of slurry composition>

[0146] A slurry composition having a solid concentration of 30 wt% was prepared by adding 97 wt% of boehmite (γ-AlO(OH)) having an average particle size of 600 nm, 2 wt% of a polyacrylamide resin (a cross-linked copolymer of acrylamide, hydroxyethyl acrylate and N-methylenebisacrylamide, denoted as 'PAM1' in Table 1, with a weight average molecular weight of 270,000 g / mol), and 1 wt% of polyethylene oxide (PEO, Mv=300,000 g / mol, CAS No: 25322-68-3, a product of Sigma-Aldrich) to water as a solvent and stirring.

[0147] <Manufacturing of diaphragm>

[0148] A separator substrate (ENPASS, SK IE Technology) with a width of 150 mm, a length of 1000 M, and a thickness of 9 μm was used. The prepared slurry composition was applied to both sides of the substrate by rod coating at a speed of 3 m / min to form a coating.

[0149] After that, the film was dried by passing through a hot air dryer at 40° C. and wound into a roll form. The total thickness of the coated separator after winding was measured to be 13 μm, and the thickness of the coating layer was 2 μm on each side.

[0150] The physical properties of the manufactured separator were evaluated and are shown in Table 1 below.

[0151] <Manufacturing of lithium secondary batteries>

[0152] A uniform negative electrode slurry was prepared by adding 95% by weight of artificial graphite as a negative electrode active material, 3% by weight of acrylic latex (solid content 20% by weight) with a Tg of -52°C as a flux, and 2% by weight of carboxymethyl cellulose (CMC) as a thickener to water and stirring. The slurry was coated on a copper foil with a thickness of 20 μm, dried, and extruded to produce a negative electrode plate with a thickness of 150 μm.

[0153] 94 wt% of LiCoO2 as a positive electrode active material, 2.5 wt% of polyvinylidene fluoride as a flux, and 3.5 wt% of carbon black as a conductive agent were added to N-methyl-2-pyrrolidone (NMP) as a solvent and stirred to prepare a uniform positive electrode slurry. The slurry was coated on an aluminum foil with a thickness of 30 μm and dried and extruded to produce a positive electrode plate with a thickness of 150 μm.

[0154] The separator was arranged between the positive electrode and the negative electrode to manufacture a pouch-type battery. An electrolyte solution of ethylene carbonate (EC) / ethyl methyl carbonate (EMC) / dimethyl carbonate (DMC) = 25:45:20 (volume ratio) including 1M lithium hexafluorophosphate (LiPF6) dissolved was injected into the assembled battery. In order to seal the opening of the aluminum packaging material, a 2Ah pouch-type lithium secondary battery was prepared by sealing the aluminum outer packaging material by heat sealing at 165°C. The physical properties of the manufactured battery were evaluated and are shown in Table 2.

[0155] [Example 2]

[0156] When preparing the slurry composition in Example 1, the same method as in Example 1 was followed except that barium sulfate having an average particle size of 500 nm was used instead of boehmite as the inorganic particles.

[0157] That is, 97 wt % of barium sulfate having an average particle size of 500 nm, 2 wt % of the polyacrylamide resin (denoted as 'PAM1' in Table 1) and 1 wt % of polyethylene oxide (PEO, Mv=300,000 g / mol, CAS No: 25322-68-3, a product of Sigma-Aldrich Corporation) were added to water as a solvent and stirred to prepare a slurry composition having a solid concentration of 30 wt %.

[0158] The physical properties of the manufactured separator and battery were evaluated and shown in Tables 1 and 2.

[0159] [Example 3]

[0160] When preparing the slurry composition in Example 1, the same method as in Example 1 was carried out except that boehmite and barium sulfate were mixed and used as inorganic particles.

[0161] That is, 50 wt% of boehmite (γ-AlO(OH)) having an average particle size of 600 nm, 47 wt% of barium sulfate having an average particle size of 500 nm, 2 wt% of the polyacrylamide resin (denoted as 'PAM1' in Table 1) and 1 wt% of polyethylene oxide (PEO, Mv=300,000 g / mol, CAS No: 25322-68-3, a product of Sigma-Aldrich Corporation) were added to water as a solvent and stirred to prepare a slurry composition having a solid concentration of 30 wt%.

[0162] The physical properties of the manufactured separator and battery were evaluated and shown in Tables 1 and 2.

[0163] [Example 4]

[0164] When preparing the slurry composition in Example 1, the same procedure as in Example 1 was followed except that two types of boehmite having different average particle sizes were used.

[0165] That is, 77 wt% of boehmite (γ-AlO(OH)) having an average particle size of 600 nm, 20 wt% of boehmite having an average particle size of 300 nm, 2 wt% of the polyacrylamide resin (denoted as 'PAM1' in Table 1), and 1 wt% of polyethylene oxide (PEO, Mv=300,000 g / mol, CAS No: 25322-68-3, a product of Sigma-Aldrich Corporation) were added to water as a solvent and stirred to prepare a slurry composition having a solid concentration of 30 wt%.

[0166] The physical properties of the manufactured separator and battery were evaluated and shown in Tables 1 and 2.

[0167] [Example 5]

[0168] When preparing the slurry composition in Example 1, the same procedure as in Example 1 was followed except that two types of barium sulfate having different average particle sizes were used.

[0169] That is, 50 wt % of barium sulfate having an average particle size of 800 nm, 47 wt % of barium sulfate having an average particle size of 500 nm, 2 wt % of the polyacrylamide resin (denoted as 'PAM1' in Table 1) and 1 wt % of polyethylene oxide (PEO, Mv=300,000 g / mol, CAS No: 25322-68-3, a product of Sigma-Aldrich Corporation) were added to water as a solvent and stirred to prepare a slurry composition having a solid concentration of 30 wt %.

[0170] The physical properties of the manufactured separator and battery were evaluated and shown in Tables 1 and 2.

[0171] [Example 6]

[0172] When preparing the slurry composition in Example 1, the same method as in Example 1 was used except that a polyacrylamide resin (labeled as 'PAM2' in the table, a copolymer of acrylic acid and acrylamide, with a weight average molecular weight of 100,000 g / mol) was used instead of the polyacrylamide resin (PAM1).

[0173] The physical properties of the manufactured separator and battery were evaluated and shown in Tables 1 and 2.

[0174] [Example 7]

[0175] When preparing the slurry composition in Example 1, the same method as in Example 1 was followed except that polyvinyl pyrrolidone (PVP, manufactured by Sigma-Aldrich, CAS Number: 9003-39-8) was used instead of the polyacrylamide resin (PA M1).

[0176] The physical properties of the manufactured separator and battery were evaluated and shown in Tables 1 and 2.

[0177] [Example 8]

[0178] When preparing the slurry composition in Example 1, the same procedure as in Example 1 was followed except that polyvinylpyrrolidone (PVP, manufactured by Sigma-Aldrich, CAS Number: 9003-39-8) was further used.

[0179] That is, 97 wt% of boehmite (γ-AlO(OH)) with an average particle size of 600 nm, 1.5 wt% of polyacrylamide resin (''PAM1'), 0.5 wt% of polyvinylpyrrolidone (PVP, manufactured by Sigma-Aldrich, CAS Number: 9003-39-8) and 1 wt% of polyethylene oxide (PEO, Mv = 300,000 g / mol, CAS No: 25322-68-3, a product of Sigma-Aldrich) were added to water as a solvent and stirred to prepare a slurry composition with a solid concentration of 30 wt%.

[0180] The physical properties of the manufactured separator and battery were evaluated and shown in Tables 1 and 2.

[0181] [Comparative Example 1]

[0182] When preparing the slurry composition in Example 1, the same method as in Example 1 was used except that a water-dispersible acrylic adhesive having a latex content of 20 wt% (containing 2 wt% of polyvinyl alcohol having a melting temperature of 220°C, a saponification degree of 99%, and a Tg of -52°C) was used alone as the adhesive.

[0183] Specifically, 97 wt % of boehmite (γ-AlO(OH)) having an average particle size of 600 nm and 3 wt % of the acrylic binder were added to water as a solvent and stirred to prepare a slurry composition having a solid concentration of 30 wt %.

[0184] The physical properties of the manufactured separator and battery were evaluated and shown in Tables 1 and 2.

[0185] [Comparative Example 2]

[0186] When preparing the slurry composition in Example 1, the slurry composition was prepared in the same manner as in Example 1 except that the polyacrylamide resin 'PAM1' was used alone as a binder.

[0187] Specifically, 97 wt % of boehmite (γ-AlO(OH)) having an average particle size of 600 nm and 3 wt % of the polyacrylamide resin 'PAM1' were added to water as a solvent and stirred to prepare a slurry composition having a solid concentration of 30 wt %.

[0188] The physical properties of the manufactured separator and battery were evaluated and shown in Tables 1 and 2.

[0189] [Comparative Example 3]

[0190] When preparing the slurry composition in Example 1, the same procedure as in Example 1 was followed except that polyethylene oxide was used alone as the binder.

[0191] That is, 97 wt% of boehmite (γ-AlO(OH), Nabaltec, Apyral AOH60) having an average particle size of 700 nm and 3 wt% of polyethylene oxide (Mv = 300,000 g / mol, CAS No: 25322-68-3, a product of Sigma-Aldrich) were added to water as a solvent and stirred to prepare a slurry composition having a solid concentration of 30 wt%.

[0192] The physical properties of the manufactured separator and battery were evaluated and shown in Tables 1 and 2.

[0193] [Comparative Example 4]

[0194] When preparing the slurry composition in Example 1, the preparation was carried out in the same manner as in Example 1 except that a polyacrylamide-based resin (denoted as 'PAM2' in the table, a copolymer of acrylic acid and acrylamide) was used alone as a binder.

[0195] That is, 97 wt% of boehmite (γ-AlO(OH)) having an average particle size of 600 nm and 3 wt% of polyacrylamide resin (denoted as 'PAM2' in the table, a copolymer of acrylic acid and acrylamide) were added to water as a solvent and stirred to prepare a slurry composition having a solid concentration of 30 wt%.

[0196] The physical properties of the manufactured separator and battery were evaluated and shown in Tables 1 and 2.

[0197]

Table 1

[0198]

[0199] Coating weight: The weight of the coating per unit area of ​​the diaphragm

[0200] As shown in Table 1 above, it can be confirmed that Examples 1 to 8 according to one aspect of the present disclosure have high Gurley air permeability, low heat shrinkage, and almost no adhesion in the horse manure paper adhesion test compared to Comparative Examples 1 to 4.

[0201] Furthermore, a lithium secondary battery was manufactured as described above using the manufactured separator, and the physical properties were measured.

[0202] [Initial resistance characteristics of lithium secondary batteries]

[0203] Each battery assembled and manufactured according to the embodiment and the comparative example was charged and then discharged using a charge / discharge cycler at a CC-CV (constant current-constant voltage) of 4.2 V. The direct current internal resistance (DC-IR) was measured by the J-Pulse method at a state of charge (SOC) of 60%.

[0204] [60℃ Storage Stability]

[0205] After each battery (2Ah Cell) assembled and manufactured according to the embodiment and comparative example was stored in a 60°C oven for 24 days, the direct current internal resistance (DC-IR) was measured by the J-Pulse method described above, and then the resistance increase rate was calculated. The resistance increase rate △R was calculated by the following formula. The resistance of each embodiment and comparative example was relatively evaluated based on comparative example 1. The higher the value, the lower the relative resistance increase rate.

[0206] △R(%)=(R2-R1) / R1×100

[0207] R1 is the initial resistance of each manufactured battery before the experiment, and R2 is the resistance after storage at 60° C. for 28 days.

[0208] The capacity retention rate ΔC was calculated by the following formula: The capacity of each Example and Comparative Example was relatively evaluated with Comparative Example 1 as a reference, and the higher the value, the higher the relative capacity retention rate.

[0209] △C (%) = [(discharge capacity after 28 days of storage in the oven - discharge capacity before storage in the oven)] / (discharge capacity before storage in the oven)] × 100

[0210] [400 cycle life]

[0211] Each battery assembled and manufactured according to the embodiment and the comparative example was charged and then discharged at 4.2V CC-CV (constant current-constant voltage) using a charge / discharge cycler.

[0212] The lithium battery was charged at 25°C at a constant current of 0.5C rate until the voltage reached 4.2V, and then charged at a constant voltage of 4.2V until the current reached 0.01C. After that, the cycle of discharging at a constant current of 0.5C until the voltage reached 3.0V was repeated 400 times. The capacity retention rate was calculated by measuring the discharge capacity of 400 cycles, and the resistance increase rate was calculated after measuring the DC-IR (Direct Current Internal Resistance) resistance using the J-Pulse method. The resistance of each embodiment and comparative example was relatively evaluated based on Comparative Example 1. The higher the value, the lower the relative resistance increase rate.

[0213] △R(%)=(R3-R1) / R1×100

[0214] R1 is the initial resistance of each manufactured battery before the experiment, and R3 is the resistance after 400 cycles.

[0215] The capacity retention rate ΔC was calculated by the following formula: The capacity of each Example and Comparative Example was relatively evaluated with Comparative Example 1 as a reference, and the higher the value, the higher the relative capacity retention rate.

[0216] ΔC (%) = [(discharge capacity after 400 cycles - initial discharge capacity) / (initial discharge capacity)] / 100

[0217] [Gas generation analysis]

[0218] Regarding the amount of gas generated, a battery charged to 100% SOC was prepared and the volume was measured with a density meter. After being stored in a 60°C oven for 10 weeks, the volume was measured in the same way. The volume change relative to the volume at the 0th week of storage (volume increase rate △V) was calculated using the following formula. The volume change in each embodiment and comparative example was relatively evaluated based on Comparative Example 1. The lower the value, the less gas was generated.

[0219] Volume increase rate △V (%) = [volume at week 10 - volume at week 0) / volume at week 0] × 100

[0220] As described above, the physical properties of the batteries of the remaining examples and comparative examples were evaluated relative to Comparative Example 1.

[0221] The results are shown in Table 2 below.

[0222]

Table 2

[0223]

[0224] As shown in Table 2, it can be confirmed that when the separators of Examples 1 to 8 according to one aspect of the present disclosure are applied, the capacity retention rate is relatively high and the resistance increase rate is low when the battery is stored at high temperature, compared with the case where the acrylic adhesive is applied as in Comparative Example 1, so that the high temperature storage stability is excellent. In addition, the capacity retention rate is high and the resistance increase rate is low in the 400 cycle characteristics, so that it can be confirmed that the long-term battery characteristics are excellent. In addition, it is confirmed that the gas generation amount is low.

[0225] In addition, Examples 1 to 8 showed more excellent physical properties than when only one binder was used as in Comparative Examples 2 to 4, thus confirming that the high temperature storage characteristics and long-term life of the battery were improved when a specific binder combination was used.

[0226] In addition, as shown in Examples 1 to 5, compared with Example 6, the combination of the three-component acrylic amide-based crosslinked copolymer and the specific inorganic particles provides a more excellent effect.

[0227] In addition, it was confirmed that the amount of gas generated was significantly reduced when barium sulfate, boehmite, and a mixture thereof were used as the inorganic particles, compared with the case where other types of inorganic particles were used.

[0228] The contents described above are merely examples of the application of the principles of the present disclosure, and other configurations may be included without departing from the scope of the present invention.

[0229] As described above, the present disclosure is described through specific matters and limited embodiments, but this is only provided to help a more comprehensive understanding of the present disclosure. The present disclosure is not limited to the above embodiments, and ordinary technicians in the field to which the present disclosure belongs can make various modifications and variations.

[0230] Therefore, the concept of the present disclosure should not be limited to the illustrated embodiments, and all equivalent or equivalent modifications to the scope of the appended claims belong to the scope of the concept of the present disclosure.

Claims

1. A diaphragm comprising a porous substrate and a coating on one or both surfaces of the porous substrate, wherein the coating comprises a water-soluble composite binder containing polyethylene oxide and a nitrogen-containing water-soluble polymer and inorganic particles.

2. The diaphragm according to claim 1, wherein: The nitrogen-containing water-soluble polymer includes any one or more selected from the group consisting of polyvinyl pyrrolidone, polyvinyl pyrrolidone copolymers and polyacrylamide resins.

3. The diaphragm according to claim 2, wherein: The polyacrylamide-based resin is a polyacrylamide-based copolymer including a unit derived from a (meth)acrylamide-based monomer and a unit derived from a comonomer.

4. The diaphragm according to claim 3, wherein: The polyacrylamide resin includes (a) structural units derived from (meth)acrylamide monomers, (b) structural units derived from hydroxyl-containing (meth)acrylic acid monomers, and (c) structural units derived from multifunctional (meth)acrylamide monomers.

5. The diaphragm according to claim 2, wherein: The weight average molecular weight of the polyacrylamide resin is 100,000 to 2,000,000 g / mol.

6. The diaphragm according to claim 1, wherein: The inorganic particles include at least one selected from boehmite and barium sulfate.

7. The diaphragm according to claim 6, wherein: The inorganic particles also include one or more inorganic particles selected from aluminum oxide, silicon dioxide, aluminum hydroxide, magnesium hydroxide, calcium oxide, magnesium oxide, titanium oxide, aluminum nitride, SrTiO3, SnO2, CeO2, NiO, ZnO, ZrO2, Y2O3 and SiC.

8. The diaphragm according to claim 1, wherein: The inorganic particles are a mixture of two or more inorganic particles having different average particle sizes.

9. The diaphragm according to claim 1, wherein: The average particle size of the inorganic particles is 200 to 1000 nm.

10. The diaphragm according to claim 1, wherein: The weight ratio of the inorganic particles to the water-soluble composite binder in the coating is 50 to 99.9:50 to 0.

1.

11. The diaphragm according to claim 1, wherein: The content of the polyethylene oxide is 1 to 50 weight % of the total content of the water-soluble composite adhesive.

12. The diaphragm according to claim 1, wherein: The content of the polyethylene oxide and the nitrogen-containing water-soluble polymer is 10 to 90:90 to 10 by weight.

13. The diaphragm of claim 1, wherein: The water-soluble composite adhesive further includes any one or more resins selected from the group consisting of polyvinyl acetate, acrylic resin, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-trichloroethylene copolymer, polyvinylidene fluoride-trifluorochloroethylene copolymer, polymethyl methacrylate, polyacrylonitrile, ethylene vinyl acetate copolymer, carboxymethyl cellulose, and polyimide.

14. The diaphragm according to claim 1, wherein: The thickness of the coating layer is 0.1 to 50% of the total thickness of the separator.

15. The diaphragm of claim 1, wherein: The coating is formed to have a thickness of 0.5 to 10 g / m 2 .

16. The diaphragm of claim 1, wherein: The porous substrate is any one selected from the group consisting of porous films, nonwoven fabrics, and woven fabrics, or a stack of two or more thereof.

17. The diaphragm of claim 1, wherein: The porous substrate has a thickness of 1 to 80 μm. 18 . A lithium secondary battery comprising the separator according to claim 1 .